A study of cohesive markers used in L1 and L2 essay writing: translation versus direct composition - Anongnad Petchprasert, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This study presents a comparative analysis of frequency rates of cohesive markers used in Thai and English written texts of graduate students who were speakers of Thai. In addition, the analysis describes the use of cohesive markers found in L1 and L2 essays with direct writing and translation. The effects of L1 transfers and participants’ metalinguistic awareness were also investigated. Specifically, the study focuses on the frequency rates of uses of cohesion based on Halliday and Hasan’s (1976) cohesion analysis such as reference, substitution, ellipsis, lexical cohesion, and conjunction in written texts. The purpose of the study is to determine the specific differences and similarities in the uses of cohesive markers in the essays. The quantitative analysis of the cohesive markers found in the English direct writing essays indicates that writers employ significantly higher frequency rates of personal reference and demonstratives than those in translation. Regarding translation method, the writers tend to rely on a repertoire of L1 rhetorical organization and language features in constructing the L2 written texts.The preponderance of cohesive markers used in L2 texts reflects the writers’ attempts to construct ideas flow with the limitations of syntactic and lexical range.